Biological Application of Novel Biodegradable Cellulose Composite as a Hemostatic Material - Xulong Zhu; Jianxiong Wang; Shuhan Wu; Tian Liu; Guangshuai Lin; Bin Shang; Jia Ma; Wudang Lu; Feifei Zhang; Jianhui Li; Jue Wang (Hindawi Limited, 2022)
Degradable hemostatic materials have unique advantages in reducing the amount of bleeding, shortening the surgical operation time, and improving patient prognosis. However, none of the current hemostatic materials are ideal and have disadvantages. Therefore, a novel biodegradable cellulose-based composite hemostatic material was prepared by crosslinking sodium carboxymethyl cellulose (CCNa) and hydroxyethyl cellulose (HEC), following an improved vacuum freeze-drying method. The resulting cellulose composite material was neutral in pH and spongy with a density of 0.042 g/cm3, a porosity of 77.68%, and an average pore size of 13.45 μm. The composite's compressive and tensile strengths were 0.1 MPa and 15.2 MPa, respectively. Under in vitro conditions, the composites were degraded gradually through petite molecule stripping and dissolution, reaching 96.8% after 14 days and 100% degradation rate at 21 days. When implanted into rats, the degradation rate of the composite was slightly faster, reaching 99.7% in 14 days and 100% in 21 days. Histology showed a stable inflammatory response and no evidence of cell degeneration, necrosis, or abnormal hyperplasia in the tissues around the embedded material, indicating good biocompatibility. In the hemorrhagic liver model, the time to hemostasis and the total blood loss in the cellulose composite group was significantly lower than in the medical gauze group and the blank control group (P<0.05). These data indicate that the novel cellulose composite is a promising implantable hemostatic material in clinical settings.